Response to pazopanib‐based combination regimen in a case of FGFR3 amplified gastric adenocarcinoma. Issue 11 (7th November 2021) - Limaye, Sewanti; Patil, Darshana; Akolkar, Dadasaheb; Srivastava, Navin; Patil, Revati; Apurwa, Sachin; Patil, Sanket; John, Jinumary; Gosavi, Rahul; Nesargikar, Prabhu; Kumar, Prashant; Datta, Vineet; et al.
Abstract: Angiogenesis inhibitors (AGI) are not presently used for the treatment of gastric cancers. This report demonstrates that angiogenesis inhibitor can be safely and effectively used in combination with cytotoxic anti‐cancer agents for treatment of Gastric cancers. Abstract : This case of Gastric Adenocarcinoma had progressed following failure of several prior lines of standard of care regimens. Multi‐analyte profiling of freshly biopsied tumor sample indicated FGFR3 amplification along with sensitivity of tumor cells towards various chemotherapy drugs. The patient received personalized combination regimen of Pazopanib with Gemcitabine and Pemetrexed which yielded significant regression of metastatic deposits.